EFFECTIVENESS OF KINESIO TAPING FOR BACK PAIN IN PREGNANT WOMEN THIRD TRIMESTER: A SCOPING REVIEW - SWASTIKA, RITA ADE; MUFDLILAH, MUFDLILAH; SURYANINGSIH, ENDANG KONI (Universitas Aisyah Pringsewu, 2025)
Back pain is a common problem experienced by pregnant women, especially in the third trimester, which can affect their quality of life and limit their ability to carry out daily activities. Back pain can occur in the lumbosacral area, which can be overcome by using non-pharmacological therapy, one of which is kinesio taping. Kinesio taping is one of the tools health workers use to relieve lower back discomfort in patients. This study examined the effectiveness of kinesio taping in helping reduce back pain in pregnant women entering the final trimester of pregnancy. Methods: A scoping review was compiled using the PICO framework and PRISMA guidelines. Results: Eight articles were extracted from the scoping review that discussed the effectiveness of kinesio taping for back pain during pregnancy in TM III (third trimester). The eight articles reached the same conclusion: kinesio taping can have a significant impact on reducing the level of discomfort experienced during TM III pregnancy due to back pain. Conclusion: Kinesio taping helps relieve discomfort in the backs of pregnant women in TM III. Keyword: Back Pain, Kinesio Taping, Pregnant Women, Third Trimester